Desiccation and recovery of periphyton biomass and density in a subtropical lentic ecosystem - doi: 10.4025/actascibiolsci.v35i3.14022 (Acta Scientiarum. Biological Sciences, 2013)
This study assessed the desiccation effects on biomass and algal density of periphyton in a subtropical lentic ecosystem. This experiment was conducted with only one in situ experimental desiccation event for 15 hours in a mature periphytic community. The periphyton after desiccation was distinct in density and biomass estimators (dry weight and chlorophyll a) when compared to the control periphyton. After the tenth day of desiccation, the community presented similar values for biomass estimators when compared to the control periphyton. The density and biomass estimators of the periphyton community was affected by the desiccation event and required about ten days to recover to pre-disturbance conditions.